Penentuan harga pokok produksi dengan menggunakan metode full costing pada Pembuatan Rumah Kayu (Studi kasus pada CV. Rajawali Tunggal Perkasa- Woloan 1 Utara) - Manein, Jeinita Olviana; Saerang, David Paul Elia; Runtu, Treesje (Universitas Sam Ratulangi, 2020)
The main cost of production was a direct and indirect amount of expenses and burdens, to produce goods or services under the right conditions and conditions for which they could be used or sold. This research was done on the CV Rajawali Tunggal Perkasa of a lumber company. The purpose of this study is to know how much profit is gained a measure of both income and sacrifice made. The kind of data used is qualitative data and the source data is the primary data. Results from studies indicate that the calculation of the principal production value to a CV Rajawali Tunggal Perkasa with a tally on the cost of production using the method full error indicates the difference of results. Based on the research, the main cost of production is based on the full yield method better at analyzing the cost of production, it is due to the calculation of principal prices of production by the full income method, not including the cost of administration and the cost of the car's rent into overhead, since those costs are a component of the company's profit assessment report.